Outcomes of Patients with IgD Multiple Myeloma Undergoing Autologous Hematopoietic Stem Cell Transplant - Pasvolsky, Oren; Milton, Denai R.; Tanner, Mark R.; Bashir, Qaiser; Srour, Samer A.; Saini, Neeraj Y.; Lin, Paul; Saeed, Arsalan; Haider, Asad A.; Ramdial, Jeremy L.; Nieto, Yago; Tang, Guilin; et al. (Transplantation and cellular therapy, 2025)
Multiple myeloma (MM) with IgD M protein (IgD myeloma) is a rare subtype of MM that is considered an aggressive form of disease with worse prognosis. Due to its rarity, there are scarce data on the outcomes of IgD myeloma following autologous hematopoietic stem cell transplantation (autoHCT). This is a single-center retrospective chart review study of IgD myeloma patients that received upfront autoHCT between 1988-2021. We conducted 1:3 propensity score matching (PSM) between patients with either IgD or IgG/IgA myeloma, according to the following variables: age, year of autoHCT (<2010, ≥2010), R2-ISS, HCT-CI (≤3, >3), induction treatment, conditioning regimen and use of maintenance treatment use (yes, no). Primary outcomes were progression-free survival (PFS) and overall survival (OS). High-risk cytogenetic abnormalities (HRCA) were defined as del17p, t(4;14), t(14;16) or 1q21 gain or amplification by fluorescence in situ hybridization (FISH). Out of a total of 3041 patients with MM who received autoHCT during the study period at our center, we identified 39 patients with IgD myeloma. Of those, 29 (74%) were male, with the median age at autoHCT of 57 years; 36% (n=14) patients had HRCA (Table 1). Prior to autoHCT, 59% of patients had achieved ≥VGPR, which increased to 78% and 82% at day 100 after autoHCT and at best post-transplant response evaluation, respectively (Figure 1). After a median follow up of 57 (range 6-202) months, the median PFS and OS for the entire cohort were 41 (95% CI 15-48) and 93 (95% CI 45-187) months, respectively (Figure 2). Three-year PFS and OS rates were 51% and 78%, respectively. In multivariable analysis, achieving ≥CR at best post-transplant response was associated with better PFS (hazard ratio (HR) 0.4, p=0.049). When comparing the IgD myeloma cohort to a matched cohort of IgG/IgA myeloma, we did not observe any difference in either PFS (HR 1.41, 95% CI 0.84-2.38; p=0.20) or OS (HR 1.01, 95% CI 0.54-1.90; p=0.98) between the two groups. This is the largest study to date to evaluate outcomes of patients with IgD myeloma who received upfront autoHCT. Despite a high proportion of patients with HRCA, the median PFS was almost 3.5 years and the median OS was >7.5 years. Using PSM, we did not find any difference in survival outcomes between IgD myeloma and a matched cohort of IgG/IgA myeloma.